Lysosomal storage diseases - Platt, Fran (Henry Stewart Talks, 2019)
Lysosomes are multifunctional, Lysosome related organelles, Complexity & functions of lysosomal proteins, Lysosomal storage diseases, Sphingolipid lysosomal storage diseases as an example, Lysosomal diseases: multimorbidity disorders, Pathogenic cascade beyond the Lysosomal System, Specific therapies approved for some diseases, Molecular mechanisms and therapeutic approaches of LSDs, Lysosomal enzymes, ERTs: approved or in advanced clinical trials, Approved small molecules: SRT & EET, Multiple gene therapy trials: enzyme deficiencies, Cellular organelles targeted by LSD therapies, Lysosomal & neurodegenerative diseases